(untitled) (Journal of Asian Development Studies, 2024)
This study explores how post-9/11 surveillance, displacement, and trauma are represented in Fatima Bhutto’s novel The Shadow of the Crescent Moon. It captures the effect of global politics and security measures on ordinary people living in a small tribal area of Pakistan. This research aims to explore the psychological trauma that arises under intense state surveillance. Moreover, it aims at unfolding how internal and external forces shape the character’s experiences and identities. This paper also utilizes Jasbir Paur’s theory of "Terrorist Assemblage" to showcase how the novel reflects the harsh realities of constant monitoring, leading to displacement of communities and deep trauma. It also explores how characters in Bhutto’s novel are subjected to both visible and invisible forms of control, examining its correlation with PTSD and C-PTSD. The purpose of this study is to show that in the novel, surveillance goes beyond mere observation and becomes a tool of power for the state and external forces, especially in conflict zones like Pakistan. So, this study will provide a critical lens on how surveillance and trauma are intertwined in the novel, contributing to broader discussions on identity, trauma, and resilience in Pakistani fiction.